Directional Shape Morphing Transparent Walking Soft Robot - Lee, Habeom; Kim, Hyeonseok; Ha, Inho; Jung, Jinwook; Won, Phillip; Cho, Hyunmin; Yeo, Junyeob; Hong, Sukjoon; Han, Seungyong; Kwon, Jinhyeong; Cho, Kyu Jin; Ko, Seung Hwan (Soft Robotics, 2019)
Transparency in electronics can provide extra functionality and esthetic impression. Transparency plays an important role in accurate soft robot control because one can directly observe target surface condition that is usually blocked by a robot's body. Nowadays, demand for soft actuators has been rapidly increasing because soft robots have attracted much attention recently. However, conventional soft actuators are usually nontransparent with simple isotropic bending, limited performance, and limited functionality. To overcome such limitations of current soft robots, we developed a novel soft shape morphing thin film actuator with new functionalities such as high transparency and unique directional responses to allow complex behavior by integrating a transparent metal nanowire heater. A figure of merit was developed to evaluate the performance and derive an optimum design configuration for the transparent actuator with enhanced performance. As a proof of concept, various transparent soft robots such as transparent gripper, Venus flytrap, and transparent walking robot were demonstrated. Such transparent directional shape morphing actuator is expected to open new application fields and functionalities overcoming limitations of current soft robots.
Keywords: Ag nanowire percolation network; Ag nanowires; Directional actuator; Directional thermal expansion; Lows-temperatures; Percolation networks; Performance; Shape morphing; Soft robot; Transparent actuator; Ag nanowire percolation network; directional actuator; directional thermal expansion; low temperature; soft robot; transparent actuator